Answer:
y' = 9x^2 + 8x^-5
Step-by-step explanation:
General Principle
y' = ax^b
y' = a*b * x^(b-1)
Solution
3x^3 = 3*3x^(3-1)
3x^3 = 9x^2
-2x^-4 = -2*-4 x ^(-4 - 1)
-2x^-4 = 8 x ^-5
Answer
y' = 9x^2 + 8x^-5
Answer:
B: quadrant 3
D: 5sqrt2
Step-by-step explanation:
1 1/4mi = 6600 and
3 3/8 t = 6750 lb.
The opposite of 17.2 from 0 on a number line would be -17.2.
Answer:
point G : (7,4)
point F : (7,1)
point J : (2,4)
point H: (5,4)
Step-by-steWhen you translate you take each point and move it how many units it asks you to move. In this problen you move each point 7 units to the right and 9 units up to get your answer.